Digital Literacy in Mediating the Influence of Education, Demography, Employment on Poverty - Liswanda, Satria; Oktavia, Rini; Zuhra, Rahma (Politeknik Statistika STIS, 2024)
This study investigated the influence of education, demography, and employment on poverty with digital literacy as a mediating variable. A structural Equation Modeling (SEM) with the Partial Least Square (PLS) method was applied. Significant indicators found are four indicators of education and digital literacy variables, two indicators of demographic and employment variables, and three indicators of poverty variables. It was found that education and employment variables had a significant influence on poverty with a negative influence. We found that no variable has a significant effect on digital literacy and there is no significant effect of digital literacy on Poverty.